Application of the Droit De Suite Principle in Dispute Settlement of Fiduciary Guarantee Agreements - Angelin Michelle Liady; Abdul Salam (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2022)
ABSTRACT      This study contains a description of the application of the droit de suite principle in the settlement of disputes over the provision of fiduciary guarantees. The problem studied in this study is how the judge's considerations regarding the application of the droit de suite principle in dispute resolution of the fiduciary guarantee agreement where the object of the guarantee is on an individual third party due to the auction of the execution of the booty and the government as a result of being used to commit a crime. The method used in this research is sociological normative legal research, by taking a statute approach to the collected legal materials. The result of this research is that the judges' considerations in some of the court's decisions in favor of individual third parties or the government are wrong. This is because the fiduciary guarantee agreement made between the fiduciary recipient (PT/creditor) and the fiduciary giver (debtor) is legally and binding based on Article 14 paragraph (3) in conjunction with Article 15 paragraph (2) and (3). Therefore, the fiduciary recipient has the authority to carry out executions based on the droi de suite principle as regulated in Article 20 of the Fiduciary Guarantee Law. In addition, based on the prioritization principle, the fiduciary recipient's actions are correct to take and execute the fiduciary guarantee object. The output to be achieved from this research is to produce scientific works in the form of research journals that can be used as reference material for other writers in the future.